Water-energy nexus: A review of methods and tools for macro-assessment. (15th January 2018) - Dai, Jiangyu; Wu, Shiqiang; Han, Guoyi; Weinberg, Josh; Xie, Xinghua; Wu, Xiufeng; Song, Xingqiang; Jia, Benyou; Xue, Wanyun; Yang, Qianqian
Highlights: 70 tools and methods are reviewed according to their nexus scopes. 35 case studies and methods used in the macro assessment are discussed. Many approaches are at the "understanding" stage of nexus analysis. Methods for governing or implementing the nexus require more attention and focus. Abstract: Over the past decade, analyzing issues within the 'water-energy nexus' has become a topic of increasing attention for the scientific and policy communities. Based on an extensive survey of recent scientific literature on the water-energy nexus, 70 studies were identified and 35 were selected as comprehensive case studies for review. The reviewed studies were classified and assessed according to groupings based on both geographic scale and their 'nexus scope'. In addition to providing a depository summary of a wide range of current existing methods and tools for water-energy nexus analysis, the paper discusses these approaches based on their main purposes. From this review, it is clear that the research on water-energy nexus has seen a significant increase in both the number of studies and the capacity of the scientific community to productively assess water and energy interlinkages at a higher resolution. At the same time, this review has also concluded that, while many studies aim to develop new methods and frameworks to comprehensively assess interactions between water, energy and other elements, none can or do provide a singular framework for performing a "nexus study". Furthermore, many researches are at the "understanding" stage with an emphasis on the quantitative analysis of the water-energy nexus. Fewer approaches are designed to support governance and implementation of technical solutions, and this is considered to a priority challenge area for the scientific community if it aims to achieve greater impact on resource policy and management. There is a clear need to improve our ability to classify and compare the capacities, strengths and weaknesses between existing approaches. This would better enable a wider group of stakeholders to utilize existing knowledge to improve their effective management of water and energy resources. It could also help focus the scientific community to more effectively improve upon the existing knowledge base and to increase focus on "governing" and "implementing" the nexus.